A comparative study on thermodynamic aspects of a mechanical drive and pneumatic drive GM cryocooler. (May 2022) - Panda, Debashis; Behera, Suraj K.; Satapathy, Ashok K.; Sahoo, R.K.; Sarangi, S.K.
Abstract: Large cooling capacity single-stage GM cryocoolers are in an enormous demand in their widespread application domains like cooling of high-temperature superconducting magnets, cryopumps, etc., nevertheless, their efficiency needs to be enhanced considerably for industrial purposes. A mathematical model is considered to be a reliable guide for the performance optimization of GM cryocooler, as it demonstrates the complex physical processes happening inside gas chambers to generate the cooling effect. In this paper, thermodynamic analysis and gas dynamic studies of a single stage mechanical drive and pneumatic drive GM cryocooler is conducted. Influence of the quiet time on the performance parameters of both types of cryocooler is demonstrated. Pressure-volume diagrams are drawn at the expansion chamber of both mechanical drive and pneumatic drive GM cryocoolers to explain the thermodynamic processes. The reason for the deviation of theoretical model pressure-volume plot from ideal pressure-volume plot is elaborated. The flow characteristics of the rotary valve on the performance parameters have been investigated. It is revealed that, the P-V power at the expansion chamber of both types GM cryocooler decreases with rise in the quiet time. However, with an increase in the quiet time, the specific cooling power of GM cryocooler increases up to certain extent. An experimental investigation is performed on a pneumatic drive GM cryocooler to substantiate the theoretical results. Highlights: Thermodynamic aspects of both mechanical drive and pneumatic drive GM cryocooler are investigated. A mathematical model is adopted to illustrate the displacer dynamics of both types of GM cryocoolers. The influence of quiet time on the performance characteristics of both cryocoolers is examined. A portable vacuum chamber and GM cryocooler are built and experimental investigation is conducted. The building procedure of the physical model of the pneumatic drive GM cryocooler is elaborated.